Central motor conduction in multiple sclerosis: evaluation of abnormalities revealed by transcutaneous magnetic stimulation of the brain. Issue 4 (April 1988) - Ingram, D A; Thompson, A J; Swash, M
Abstract : Magnetic stimulation of the brain and spinal column was used to assess conduction in the descending central motor pathways controlling arm and leg muscles of 20 patients with multiple sclerosis, and 10 normal subjects. The multiple sclerosis patients had relapsing and remitting disease but all were ambulant and in stable clinical remission. Increased central motor conduction times (CMCTs), up to three times normal, were frequently encountered in multiple sclerosis patients and in leg muscles these correlated closely with clinical signs of upper motor neuron disturbance; in the upper limb muscles a higher proportion of subclinical lesions was present. Weak muscles were almost invariably associated with abnormal central conduction but increased CMCTs were also found for 52 of the 104 muscles with normal strength. CMCTs for lower limb muscles were directly related (p less than 0.005) to functional motor disability (Kurtzke and Ambulatory Index Scales). No patient developed clinical evidence of relapse during follow-up of at least 8 months. Magnetic brain stimulation is easy to perform, painless, and safe, and provides clinically relevant information in the diagnosis and monitoring of multiple sclerosis patients.